Comparative study of SPI and SPEI drought indices for meteorological drought assessment in Mauritius - Vimal Mungul; Manta D. Nowbuth (Jàmbá)
Drought is a global issue affecting many countries, including Mauritius, which is vulnerable to this natural hazard. This study compares two robust drought indices: the Standardised Precipitation Index (SPI) and its variant the Standardised Precipitation Evapotranspiration Index (SPEI) using statistical techniques, to determine the most appropriate drought assessment tool for Mauritius, as a Small Island Developing State (SIDS). The study utilised monthly averaged rainfall, maximum and minimum temperature data from six meteorological stations spanning 1971–2017. Standardised Precipitation Index and SPEI values were computed at 1, 3, 6 and 12-month timescales using the SPEI package in R−Programming. Three statistical tests: Pearson’s Correlation, Cohen Kappa’s Statistics and Bland-Altman were applied to assess the relationship between these indices. Strong correlations were observed with Pearson’s correlation showing (r  0.9, p  0.01), Cohen’s Kappa test revealed ‘almost perfect agreement’ with values reaching +0.95 at 3-month timescale and +0.94 for the remaining timescales, finally Bland-Altman plots further confirmed acceptable agreement. This study concluded that both SPI and SPEI could effectively assess drought in Mauritius.